KASUS NOMINA BERUNSURKAN KONSONAN AKHIR SEMIVOKAL (ISM MU’TALL AKHIR) DALAM AL-QURAN JUZ 29 DAN 30 (ANALISIS SINTAKSIS) (Lisanul Arab: Journal of Arabic Learning and Teaching, 2015)
Abstrak ___________________________________________________________________ Ism mu’tall akhir adalah ism yang konsonan akhirnya berupa konsonan semivokal atau illat (alif, waw dan ya’).  Ism ini terdiri atas ism maqshu>r, ism manqu>sh dan ism mamdu>d. Ism maqshu>r adalah ism mu’rab yang huruf akhirnya adalah alif permanen, baik dilambangkan dengan huruf alif tegak atau mirip huruf ya’ . Adapun ism manqu>sh adalah ism mu’rab yang diakhiri dengan huruf ya’permanen asli dan huruf sebelumnya bercharakat kasrah. Sedangkan Ism Mamdu>d adalah ism mu’rab yang huruf akhirnya adalah hamzah dan didahului oleh Alif tambahan.Dalam penelitian ini,peneliti membahas I’rab dari nomina berunsurkan konsonan akhir semivokal dalam Al-Quran Juz 29 dan 30 karena pada Juz 29 dan 30 terdapat banyak sekali nomina-nomina berunsurkan konsonan akhir semivokal.   Abstract ___________________________________________________________________Ism mu’tall akhir is a semivocal ended noun. The noun consist of ism maqshu>r, manqu>sh and mamdu>d. ism maqshu>r is a derivated noun that be ended by permanent alif,  symbolized by  upright one or similar with ya’. As ism manqu>sh is a derivated noun that be ended by  permanent ya’ and ism mamdu>d is a derivated noun that be ended by  hamzah and added alif before. The research is about semivocal ended noun in 29th and 30th juz of Al-Quran. The amount of data is much there.The purpose of the research is to describe types, functions and gramatical signs of semivocal ended noun. It used qualitative approach with descriptive type. The data is semivocal ended noun and the source is 29th and 30th juz of Al-Quran.  The data collecting technique is documentary and the instruments are data card and data recapitulation table.The results of the research are: the researcher found four of six semivocal ended noun. Beside that, he also found 7 nominative functions, 7 accusative functions and 5 genetive functions. From the grammatical side, he also found 10 nominative  nouns with real vocal /u sign, 15 nominative nouns with unreal vocal /u sign and a noun with /w/ sign. He also found 10 accusative nouns with real vocal /a sign and 25 accsative nouns with unreal vocal /a sign and 13 genetive nouns with real vocal/ i sign and 23 genetive nouns with unreal vocal/ i sign.